A modular web framework for socio-CPS-based condition monitoring - Fleischmann, Hans; Kohl, Johannes; Franke, Jörg (IEEE International Workshop on Factory Communication Systems - Proceedings, WFCS, 2016)
The increasing complexity of production plants in the context of Industry 4.0 poses new challenges with regards to technical maintenance. In industrial domains, Condition Monitoring Systems (CMS) enable fault-tolerant, predictable production systems. Unfortunately, CMS development is challenging due to the distribution of computational tasks among heterogeneous industrial Internet of Things and Services (IoTS)-architectures. It is usually started from scratch, which is time-consuming and error-prone. In times of IoTS the employee as a maintenance worker, who ensures the availability of production machinery, is still important. In order to address these challenges, we propose a modular framework for web-based condition monitoring and fault diagnostics. The implementation relies on technologies such as Hypertext Markup Language 5 (HTML5), JavaScript (JS) and node.j s as well as industrial internet communication standards. Finally, verification and validation are performed in a case study on a modular robot cell for the inspection of electronic assemblies.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Communication Standards; Condition Monitoring Systems; Distributed Application Platforms; Maintenance; Socio-Cyber-Physical Systems